Model for stars of interacting bosons and fermions - Sousa, Cláudio M. G. de; Tomazelli, J. L. [UNESP]; Silveira, Vanda (American Physical Society (APS), 1998)
In this paper we introduce a current-current type interaction term in the Lagrangian density of gravity coupled to complex scalar fields, in the presence of a degenerated Fermi gas. For low transferred momenta, such a term, which might account for the interaction among boson and fermion constituents of compact stellar objects, is subsequently reduced to a quadratic one in the scalar sector. This procedure enforces the use of a complex radial field counterpart in the equations of motion. The real and the imaginary components of the scalar field exhibit different behavior as the interaction increases. The results also suggest that the Bose-Fermi system undergoes a phase transition for a suitable choice of the coupling constant.